2016
DOI: 10.1016/j.jval.2016.09.869
|View full text |Cite
|
Sign up to set email alerts
|

Supply-Side and Demand-Side Policies for Biosimilars: An Overview in 10 European Member States

Abstract: Objective: This study aimed to provide an overview of biosimilar policies in 10 EU MSs. Methods: Ten EU MS pharmaceutical markets (Belgium, France, Germany, Greece, Hungary, Italy, Poland, Spain, Sweden, and the UK) were selected. A comprehensive literature review was performed to identify supply-side and demand-side policies in place in the selected countries. Results: Supply-side policies for biosimilars commonly include price linkage, price re-evaluation, and tendering; the use of internal or external refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…• biosimilar price discount over original biologic price, the number of analogues, and the distribution channel were not correlated with the biosimilar uptake; • average generic price discount over originator and the number of biosimilars show a trend toward statistical significance for correlation with biosimilar uptake, but do not reach the significance threshold; • incentive policies and the date of first biosimilar market entry were correlated with biosimilar uptake [17] , although other studies suggested that incentives might differently impact product classes [36] .…”
Section: Article In Pressmentioning
confidence: 80%
See 1 more Smart Citation
“…• biosimilar price discount over original biologic price, the number of analogues, and the distribution channel were not correlated with the biosimilar uptake; • average generic price discount over originator and the number of biosimilars show a trend toward statistical significance for correlation with biosimilar uptake, but do not reach the significance threshold; • incentive policies and the date of first biosimilar market entry were correlated with biosimilar uptake [17] , although other studies suggested that incentives might differently impact product classes [36] .…”
Section: Article In Pressmentioning
confidence: 80%
“…By considering one framework [17] , policies concerning biosimilars can be divided into "demand-side " and "supply-side " ones. Demand-side measures aim to steer the prescription of biological drugs towards the biosimilar alternative, while supply-side policies focus on the conditions associated with provision of the product.…”
Section: Surfing the Bio-wave: Tools To Foster Biosimilars' Prescriptionsmentioning
confidence: 99%
“…The full description of the results for the literature review was presented elsewhere [25]. Incentive policies applied to biosimilars are heterogeneous across countries.…”
Section: Resultsmentioning
confidence: 99%
“…The search strategy used free search terms and was performed between October and November 2015. The full description of the methodology for the literature review was presented elsewhere [25]. The search strategy was performed in the following databases: MEDLINE; Embase; The Cochrane library; Generics and Biosimilars initiative (GaBi) journal and website; and the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) and Health Technology Assessment International (HTAi) websites for conference abstracts.…”
Section: Literature Reviewmentioning
confidence: 99%